Complete genome sequence and SNPs of Raja pulchra (Rajiformes, Rajidae) mitochondria. (3rd July 2016) - Hwang, Jae Yeon; Jin, Gwi-Deuk; Park, Jongbin; Kim, Heebal; Lee, Chang-Kyu; Kwak, Woori; Nam, Bo-Hye; An, Cheul Min; Park, Jung Youn; Park, Kyu-Hyun; Huh, Chul-Sung; Kim, Eun Bae
Abstract: Mitochondrial genomes were sequenced from five Raja pulchra individuals, and single-nucleotide polymorphisms (SNPs) were identified by comparing previously announced sequences in this study. Total 117 SNPs were detected and they were present in 2 rRNA genes, 9 tRNA genes, 13 protein coding genes and non-coding region. One deleted polymorphic site, which was located in 16S rRNA gene, was observed in two individuals. Six polymorphic sites were non-synonymous SNPs, which were distributed in ND1, ND2, ATP6 and ND4 gene. Phylogenic analysis validated current taxa. The genome sequences of R. pulchra mitochondria could be comparable information for understanding species divergence and genomic variation among the populations.